Sistem Bertani Padi Sawah Bagi Orang Bugis di Desa Nelombu Kecamatan Mowewe Kabupaten Kolaka Timur - Irhan Arno; Sarlan Adi Jaya (JURNAL KABANTI: Kerabat Antropologi, 2023)
This research aims to know and describe the way of farming of Bugis people in Nelombu Village and why Bugis people in Nelombu Village still maintain the way of farming rice fields. The method used in this research is descriptive qualitative method in which researchers try to describe, describe and explain how the process of farming rice fields for the Bugis. Using purposive techniques and direct field observations. The data collected was then analyzed using the theory of cultural ecology by Julian H. Steward. The results of this study are: 1). How to farm rice paddies in the Bugis where holding tudang sipulung (sitting together with deliberation), ma'jama galung (land management), mattabela (scattering seeds), mappajo-pajo (installation of scarecrows), mappasule' (transferring seedlings to land that does not grow), mappamula ase (beginning of harvest), mingala ase (harvesting on black sticky rice), mappeppe ase pulu lotong (threshing sticky rice) and mallampu ase pulu (stripping the skin on sticky rice). 2). The reason why Bugis people still maintain the method of farming paddy rice is because firstly, farming paddy rice is a tradition that is passed down. Secondly, farming paddy rice is supported by the natural environment.